Augmented reality-based stem learning to enhance elementary school students' higher-order thinking skills - Chairan Zibar L. Parisu; Aspin Aspin; Asharif Suleman (Jurnal Konseling dan Pendidikan, 2025)
This study aims to assess the effectiveness of AR-assisted science learning with a STEM approach in improving students' HOTS compared to conventional learning. The method used was a quasi-experimental design with a Pretest–Posttest Control Group involving two classes: an experimental class (AR-STEM) and a control class (conventional). The instruments consisted of a HOTS test (domains C4–C6), an engagement observation sheet, and a student response questionnaire. The results showed an average HOTS posttest score of 82.23 for the experimental class compared to 67.09 for the control class; The average N-Gain value in the experimental class was 0.64 (medium-high category according to learning criteria), while the control class was 0.36 (medium-low category). The independent samples t-test showed a significant difference in the posttest score and N-Gain (p < 0.001). This quantitative finding is supported by very positive student responses (average > 3.50) in the aspects of media attractiveness, ease of use, learning engagement, and perception of HOTS improvement. Interpretation of the results: the increase in N-Gain from 0.36 to 0.64 in the experimental group indicates a meaningful learning change, namely an increase in higher-order thinking skills in a range of effects that are practically substantial, not just statistically significant. The highly significant difference (p < 0.001) strengthens the finding that the integration of AR with the STEM approach not only increases engagement, but also encourages the development of students' analytical, evaluation, and creative skills more effectively than conventional methods. These findings are consistent with the idea that AR provides visual representations and real interactions for exploring scientific phenomena, while the STEM approach structures activities that require critical thinking and integrated problem-solving—a complementary combination to build HOTS. In conclusion, AR-STEM learning is an effective and contextual strategic alternative to increase HOTS, engagement, and learning motivation in science learning, and is relevant to the demands of the Independent Curriculum.